Primary care availability affects antibiotic consumption: Evidence using unfilled positions in Hungary - Anikó Bíró; Peter S. Elek (Hungarian Academy of Sciences, Institute of Economics, 2018)
Using administrative data from Hungary, we analyse the effect of general practitioner (GP) care availability on the consumption of antibiotics. We exploit the geographical and time variation in unfilled GP positions as a source of exogenous variation in the availability of primary care. According to our estimates from fixed effects panel regressions, if the single GP position of a village becomes unfilled, the days of therapy (DOT) as well as public expenditures on antibiotics decrease by 3.2-4.1%. The negative effect on antibiotic consumption is stronger in smaller settlements, in settlements where secondary care is less available, and where antibiotics were previously overprescribed. The quality of prescribing behaviour measured by the ratio of narrow-spectrum to broad-spectrum antibiotics deteriorates significantly as a consequence of worse primary care availability. The number of GP consultations decreases by 9.8%, but prescribed antibiotic DOT per GP visit goes up by 7.2%.
Keywords: C23; I10; I11; 330; Administrative panel data; Antibiotics; Primary care availability; Quality of antibiotic prescription; Unfilled general practices